Independent Evidence for the Preservation of Endogenous Bone Biochemistry in a Specimen of Tyrannosaurus rex - Jennifer Anné; Aurore Canoville; Nicholas P. Edwards; Mary H. Schweitzer; Lindsay E. Zanno (Biology, 2023)
Biomolecules preserved in deep time have potential to shed light on major evolutionary questions, driving the search for new and more rigorous methods to detect them. Despite the increasing body of evidence from a wide variety of new, high resolution/high sensitivity analytical techniques, this research is commonly met with skepticism, as the long standing dogma persists that such preservation in very deep time (>1 Ma) is unlikely. The Late Cretaceous dinosaur Tyrannosaurus rex (MOR 1125) has been shown, through multiple biochemical studies, to preserve original bone chemistry. Here, we provide additional, independent support that deep time bimolecular preservation is possible. We use synchrotron X-ray fluorescence imaging (XRF) and X-ray absorption spectroscopy (XAS) to investigate a section from the femur of this dinosaur, and demonstrate preservation of elements (S, Ca, and Zn) associated with bone remodeling and redeposition. We then compare these data to the bone of an extant dinosaur (bird), as well as a second non-avian dinosaur, Tenontosaurus tilletti (OMNH 34784) that did not preserve any sign of original biochemistry. Our data indicate that MOR 1125 bone cortices have similar bone elemental distributions to that of an extant bird, which supports preservation of original endogenous chemistry in this specimen.